EKOTEOLOGI DALAM EDUKASI LINGKUNGAN:DAUR ULANG SAMPAH DAN PENANAMAN BIBIT KKN SUKOGIDRI - Moh. Riki Nur Rivaldi; Novia Ulfa Isnaini; Isma Sauja Ayugya; Qibtiyah Ayu Maryati; Siti Sekar Liyanti; Yunita Nabila Greesisca; Moh. Kafin Adzka; Ratna Aprilia; Laila Salsabila; Zainal Arifin (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
Environmental damagecontinues to be an increasingly worrying issue. In response to this,the Ministry of Religious Affairs has made environmental issues a matter that must beresolved through priority eco-theology programs. This service was carried out to support the Ministry of Religious Affairs' ecotheology programin Sukogidri Village through a socialization program and nature school activitieson waste recycling and planting vegetable seeds for elementary school students. This community service used the participatory action research (PAR) method by directly engagingin discussions about the problems encountered in the community service andfacilitating their resolution. The results of this community service showthat the issue of waste is an important problem to be solved, and that fosteringan environmentally friendly mindset in children must also be done. The results of the socialization and nature school activities showed that elementary school students were very enthusiastic inparticipating in these activities. They listened attentivelyduring the socialization, scrambled to answer questions, and one student evenasked to take his work home to show hisparents. Positive responses also came from elementary school teachers. They fully supportedthis community service activity.